Reformasi Birokrasi: Meningkatkan Efektivitas Manajemen Sumber Daya Manusia di Sektor Publik - Leni Rohida; Adinda A (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Bureaucratic reform is an effort of renewal and fundamental change in the system of governance aimed at creating governance that is more effective, efficient, transparent, and oriented toward public service. However, in recent years, the implementation of bureaucratic reform at the local level has shown that the structuring of governmental institutions still requires significant improvement, indicating the need for a paradigm shift in governance. This study aims to identify the implementation of bureaucratic reform in optimizing the performance of public services in Buyut Village, Gunung Jati Subdistrict, Cirebon Regency. This research employs a descriptive empirical method with a qualitative approach. Data analysis was conducted through data reduction, systematic data reading, and conclusion drawing. The theoretical framework refers to public policy theory with the concept of optimization as proposed by Sirigoringo (2005), which includes elements of objectives, decision alternatives, and constraining resources. The results indicate that the performance of public services in Buyut Village, Gunung Jati Subdistrict, Cirebon Regency has not yet been optimal. Although certain achievements have been made in service delivery, there are still indicators that require optimization, particularly in the aspect of constraining resources. This condition is reflected in complaints from some residents of Buyut Village regarding the lack of adequate facilities, infrastructure, and service-supporting amenities to facilitate village government services to the community. Based on these findings, efforts to optimize bureaucratic reform at the village level should prioritize the provision of adequate facilities, infrastructure, and supporting resources before bureaucratic reform policies are implemented. Thus, bureaucratic reform is expected to improve the quality of public services and provide tangible benefits for rural communities while fostering public trust in government officials. Furthermore, community involvement and the enhancement of bureaucratic capacity are essential elements to ensure the sustainability of the bureaucratic reform agenda at the village governance level.